Designing for behavior change : applying psychology and behavioral economics - Wendel, Stephen (Ascent Audio, 2023)
Designers and managers hope their products become essential for users-integrated into their lives like Instagram, Lyft, and others have become. Such deep integration isn't accidental: it's a process of careful design and iterative learning, especially for technology companies. This guide shows you how to apply behavioral science-research that supports many products-to help your users achieve their goals using your product. In this updated edition, Stephen Wendel, head of behavioral science at Morningstar, takes you step-by-step through the process of incorporating behavioral science into product design and development. Product managers, UX and interaction designers, and data analysts will learn a simple and effective approach for identifying target users and behaviors, building the product, and gauging its effectiveness. - Learn the three main strategies to help people change behavior - Identify behaviors your target audience seeks to change-and obstacles that stand in their way - Develop effective designs that are enjoyable to use - Measure your product's impact and learn ways to improve it - Combine behavioral science with data science to pinpoint problems and test potential solutions.